The importance of anatomical localization of non‐small cell lung carcinoma in predicting mediastinal lymph node metastasis. Issue 2 (5th October 2021) - Kucuker, Merve; Kucuker, Kadir Alper; Guney, Isa Burak; Durgun, Behice
Abstract: Bronchopulmonary segmental location of non‐small lung carcinomas is closely related to metastatic lymph node foci in the mediastinum. Our aim was to investigate the relationship between the anatomical locations of pulmonary masses on the bronchopulmonary segmental base and metastatic lymph node regions in non‐small cell lung cancer using preoperative 18F‐FDG PET/CT images. Ninety patients newly diagnosed with non‐small cell lung carcinoma and referred to PET/CT imaging for staging were included in the study. Tumoral masses that could be evaluated visually and mediastinal node metastases were identified in 18F‐FDG PET/CT images, then the relationship between them was investigated statistically. The diagnostic power of 18F‐FDG PET/CT of mediastinal nodes was also revealed. Seventy‐four males (82.2%) and sixteen females (17.8%) were enrolled in the study. Half of the patients were diagnosed as adenocarcinoma (50%). Investigation of the tumor location and mediastinal metastatic nodes revealed a statistically significant relationship between the apicoposterior segment of the left superior lobe and the left upper and lower paratracheal, subaortic, paraaortic, and left hilar regions according to the IASLC map. The sensitivity, specificity and accuracy of 18F‐FDG PET/CT in the mediastinal nodes were 69.2%, 66.6%, and 68%, respectively. There was no statistically significant relationship between tumor location and 8th TNM Stage. Anatomical locations of non‐small cell lung carcinomas can affect the disease stage and prognosis because of their tendency to metastasize to some mediastinal regions. However, this relationship needs to be investigated in larger study groups.